A study of the factors which influence digital transformation in Kibs companies - Marino-Romero, Jorge Alberto; Palos-Sanchez, Pedro Ramiro; Velicia-Martin, Félix Antonio; Rodrigues, Ricardo Gouveia (Frontiers in Psychology, 2022)
Eighteen interviews were used in this research to inductively conceptualize the factors that influence digital transformation (DT) in Kibs companies that provide multidisciplinary Knowledge Intensive Business Services. Two main groups were identified: factors of DT and use in the new digital environment. Using the findings obtained, a comparison was made with the existing literature and the most relevant aspects of DT as a disruptive phenomenon which can generate intra-organizational competitive advantage are exposed.